MCSA/MCSE 2003 JumpStart : computer and network basics - Donald, Lisa (SYBEX, 2003)
Get Up To Speed for Windows XP and Server 2003 Training-Fast! MCSA/MCSE 2003 JumpStart gives you the solid grounding you need to approach MCSA and MCSE certification training with confidence:Microprocessors and memoryData storageInput/output devicesHardware configurationDesktop operating systemsDOS and Windows basicsThe OSI reference modelCommon network models and architecturesInternetworking protocolsNetwork operating systemsWindows XP and Server 2003 platformsActive Directory basicsWindows XP and Server 2003 account and resourc.